Experimental and Numerical Study of Ballistic Impact Performance on Steel Plate Structures - Alawsi, Muhanad Hamed Mosa; Al-Zobaede, Ali Muslem Abed; Al-Obaidi, Salah M. Ali (Journal of Engineering and Sustainable Development, 2025)
High-strength steel plates are commonly employed in civil and military vehicles to provide ballistic protection against various threat levels. In this work, experimental tests involved shooting a 2 mm steel target (150×150 mm) with a Parabellum 9 × 19 full metal jacket projectiles moving at a ballistic velocity of 370 m/s. On the other hand, numerical work was conducted to simulate the same event using LS-DYNA, an explicit finite element code. The objective of this work was to demonstrate the capability of LS-DYNA software in simulating the effects of ballistic impact and analyzing the performance of steel plate armor. The numerical analysis demonstrated that all constitutive relations effectively predicted the qualitative behavior of the physical mechanisms during perforation. The influence of fracture criteria on numerical simulations of the perforation process was investigated. Detailed discussions were provided regarding the reasons behind these findings. For practical applications, the suitable selection of the type of constitutive model and criterion of fracture employing the finite element method (FEM) leads to an excellent agreement with the experimental results of projectile impacts on steel targets under the same conditions.